The One-Sided Tale of Poor Latin America - Cerveira Kampff, Luiza (Journal of International Students, 2023)
The experience of participating in a mobility program is both enriching and shocking. While facing different identities and asymmetrical relations of power, the international student from the Global South is forced to reanalyze his or her identity in the world. The politics of racialization and the dichotomy between the politics of belonging and of bordering make those who study abroad realize the stereotypes of the country they are nationals of and the prejudice their co-citizens may suffer. As such, this text is my narrative as a Brazilian student in the Middle East living in a community predominantly constituted by Europeans, describing the process of realization of my identity as a Global South and Latin American citizen.